A strong converse inequality for the iterated Boolean sums of the Bernstein operator - DRAGANOV, Borislav R. (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
We establish a two-term strong converse estimate of the rate of approximation by the iterated Boolean sums of the Bernstein operator. The characterization is stated in terms of appropriate moduli of smoothness or K-functionals. Mathematics Subject Classification (2010): 41A10, 41A17, 41A25, 41A27, 41A35, 41A40. Received 13 November 2019; Accepted 18 February 2020.